Ground target tracking using UAV with input constraints - Zhu, Senqiang (2013)
This paper provides a solution to the problem of ground target tracking using an unmanned aerial vehicle (UAV) with control input constraints. Target tracking control with input constraints is an important and challenging topic in the study of UAVs. In order to achieve precise target tracking in the presence of constant background wind and target motion, this paper proposes a saturated heading rate controller based on a guidance vector field while the airspeed is held constant. This proposed approach guarantees the global convergence of the UAV to a desired circular orbit around a target. To estimate unknown constant background wind and target motion, an adaptive observer with bounded estimate is developed. Simulation results demonstrate the effectiveness of the proposed approach.